The Betrayal Aversion Elicitation Task: An Individual Level Betrayal Aversion Measure. - Jason Aimone; Sheryl Ball; Brooks King-Casas (PLoS ONE, 2015)
Research on betrayal aversion shows that individuals' response to risk depends not only on probabilities and payoffs, but also on whether the risk includes a betrayal of trust. While previous studies focus on measuring aggregate levels of betrayal aversion, the connection between an individual's own betrayal aversion and other individually varying factors, including risk preferences, are currently unexplored. This paper develops a new task to elicit an individual's level of betrayal aversion that can then be compared to individual characteristics. We demonstrate the feasibility of our new task and show that our aggregate individual results are consistent with previous studies. We then use this classification to ask whether betrayal aversion is correlated with risk aversion. While we find risk aversion and betrayal aversion have no significant relationship, we do observe that risk aversion is correlated with non-social risk preferences, but not the social, betrayal related, risk component of the new task.